ANALISA USER REQUIREMENT SPESIFICATION SISTEM INFORMASI AKADEMIK ON-LINE - Nurjoko, - (Jurnal Informatika, 2011)
System information (SI) has been very instrumental in improving competitive advantage (Competitive Advantage), to create value for the organization. not least in informatics and Business Darmajaya (IBI), a Higher Education Institution that made the Academic Information System (AIS) to support his efforts. To achieve this requires a development of the Academic Information System (AIS) are structured. Academic information systems that exist today with the new integrated financial information system and have not been able to meet all the needs of the academic information required by internal users and external users. Therefore, analysis of the needs of academic information systems is necessary in IBI darmajaya, where the activities of academic services is the responsibility of the work of a firm called BAAK (Bureau of Academic Administration and kemahasiswaaan) and academic information system development is the responsibility of a unit of the Unit Executive technical Computer Center (UPT Puskom). Academic information system requirements analysis in this paper uses the User Requirements Analysis Method (interviews, questionnaires, observation, analysis procedure, and document survey).Keywords: Requirements Analysis, User Requirement specification